URBAN TOURISM GOVERNANCE FOR ENVIRONMENTAL SUSTAINABILITY LEGAL REVIEW IMPLEMENTATION OF ENVIRONMENTAL PRESERVATION THROUGH TOURISM - Afrinaldy Rustam; Asrinaldi; Hendri Keswara; Kamaruddin (International Conference On Law And Social Sciences, 2024)
This article discusses the importance of tourism governance education in the context of environmental sustainability, with a focus on environmental legal aspects. The rapidly growing presence of tourism often causes negative impacts on the environment, including degradation of natural resources and damage to ecosystems. In order to overcome this problem, an environmental law approach is important to ensure that tourism development is carried out with environmental sustainability in mind. This article also highlights the role of education in promoting sustainable tourism governance. Tourism management education can help increase public, manager and tourist visitor awareness of the importance of preserving the environment. Apart from that, education can also form responsible attitudes and behavior towards the environment. By combining environmental law approaches and tourism governance education, it is hoped that a solid framework for sustainable tourism development can be created. This research uses descriptive analysis methods to evaluate the concept of environmental law and its application in the context of tourism management education. The findings from this research can provide in-depth insight into how educational efforts can support sustainability principles in tourism management.